Evolution and Innovation of Inlay Materials in Oral Restoration: Focus on Biocompatibility and Functional Integration - Wang, Dan (International Journal of Materials Science and Technology Studies, 2025)
Inlays, as a conservative and aesthetic oral restoration method, have gradually replaced traditional fillings in the treatment of moderate to large dental defects due to their superior marginal adaptability, mechanical stability, and aesthetic performance. Material science is the core driving force for the development of inlay technology, and the performance optimization of traditional materials and the emergence of new materials have continuously expanded the clinical application scope of inlays. This systematic review summarizes the latest progress in the material science of oral restoration inlays, focusing on the performance improvement of classic materials (resin, ceramic, metal), the development of composite materials, and the application of functional materials. We also analyze the clinical selection strategies of inlay materials and future development directions to provide evidence-based references for oral restoration practice. A comprehensive literature search was conducted in PubMed, Embase, and Cochrane Library using keywords including "inlay material", "oral restoration", "ceramic inlay", and "resin composite inlay". Relevant studies published between 2018 and 2025 were included, and the final analysis covered 40 high-quality articles (randomized controlled trials, systematic reviews, and laboratory studies).